Accelerated shifts in terrestrial life zones under rapid climate change. (13th November 2021) - Elsen, Paul R.; Saxon, Earl C.; Simmons, B. Alexander; Ward, Michelle; Williams, Brooke A.; Grantham, Hedley S.; Kark, Salit; Levin, Noam; Perez‐Hammerle, Katharina‐Victoria; Reside, April E.; Watson, James E. M.
Abstract: Rapid climate change is impacting biodiversity, ecosystem function, and human well‐being. Though the magnitude and trajectory of climate change are becoming clearer, our understanding of how these changes reshape terrestrial life zones—distinct biogeographic units characterized by biotemperature, precipitation, and aridity representing broad‐scale ecosystem types—is limited. To address this gap, we used high‐resolution historical climatologies and climate projections to determine the global distribution of historical (1901–1920), contemporary (1979–2013), and future (2061–2080) life zones. Comparing the historical and contemporary distributions shows that changes from one life zone to another during the 20th century impacted 27 million km 2 (18.3% of land), with consequences for social and ecological systems. Such changes took place in all biomes, most notably in Boreal Forests, Temperate Coniferous Forests, and Tropical Coniferous Forests. Comparing the contemporary and future life zone distributions shows the pace of life zone changes accelerating rapidly in the 21st century. By 2070, such changes would impact an additional 62 million km 2 (42.6% of land) under "business‐as‐usual" (RCP8.5) emissions scenarios. Accelerated rates of change are observed in hundreds of ecoregions across all biomes except Tropical Coniferous Forests. While only 30 ecoregions (3.5%) had over half of their areas change to a different life zone during the 20th century, by 2070 this number is projected to climb to 111 ecoregions (13.1%) under RCP4.5 and 281 ecoregions (33.2%) under RCP8.5. We identified weak correlations between life zone change and threatened vertebrate richness, levels of vertebrate endemism, cropland extent, and human population densities within ecoregions, illustrating the ubiquitous risks of life zone changes to diverse social–ecological systems. The accelerated pace of life zone changes will increasingly challenge adaptive conservation and sustainable development strategies that incorrectly assume current ecological patterns and livelihood provisioning systems will persist. Abstract : Climate change poses direct challenges for biodiversity, livelihoods, and human health. Yet how climate change impacts broad ecosystem stability is uncertain. We quantify future ecosystem changes – or 'life zone' shifts – under climate change and compare them with historical changes. Approximately 62 million km 2 (42.6%) of land is projected to change to a different life zone under business‐as‐usual emissions by 2070—more than double the area that shifted in the last century. The most impacted biomes include boreal and temperate coniferous forests and montane grasslands and shrublands. Projected life zone shifts present a threat to people and nature around the world.